2021
DOI: 10.1097/mpg.0000000000003174
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Selenium Status in Infants on Parenteral Nutrition Therapy

Abstract: Introduction: Selenium is an essential micronutrient that must be supplemented in infants and young children on exclusive parenteral nutrition (PN). We examined selenium status and clinical factors associated with a deficiency in infants on PN. Methods: This was a retrospective cohort study of pediatric patients receiving PN with routine monitoring of selenium status. Deficiency was diagnosed using age-based norms of plasma selenium status. Associations between selenium deficiency and the following clinical fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Similarly, many other studies have reported lower blood selenium level in preterm infants than term infants [10,11,23]. Another study showed more frequent selenium deficiency in extremely low birth weight infants and very low birth weight infants compared to normal birth weight infants [24].…”
Section: Preterm Infantsmentioning
confidence: 68%
“…Similarly, many other studies have reported lower blood selenium level in preterm infants than term infants [10,11,23]. Another study showed more frequent selenium deficiency in extremely low birth weight infants and very low birth weight infants compared to normal birth weight infants [24].…”
Section: Preterm Infantsmentioning
confidence: 68%
“…11 ELBWIs have a higher risk of selenium deficiency because they tend to have shorter GA, feeding intolerance, and slow increases in enteral nutrition (EN). 18 Recently, Rao et al 27 reported that the odds of selenium deficiency were higher in ELB-WIs (odds ratio = 17.84, 95% CI [4.04-78.72]; P <.001) compared with reference birth weight infants. In this study, GA (P = .096), birth weight (P = .131), and the proportion of ELBWIs (P = .053) in both groups were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the symptoms of this disease were reversed in patients receiving Se supplements as parenteral nutrition (intravenous injections) [ 63 ]. Se-containing food supplements are currently considered as an integral part of parenteral nutrition [ 64 , 65 ].…”
Section: Effects Of Selenium Deficiency and Excess On Human Organismmentioning
confidence: 99%